Diagnostic performance of the classic symptom “abdominal pain before vomiting” for pediatric acute appendicitis - Hiroki Kitaoka; Hayato Chikai; Keiko Watanabe; Hiroto Ida; Tadayuki Kumagai (Pediatrics and Neonatology)
Background: Acute appendicitis is the most common type of acute abdomen that requires surgical intervention in children. According to general pediatric textbooks, the presence of vomiting before abdominal pain is considered a classic patient history item for excluding acute appendicitis. However, its diagnostic performance in the pediatric population has yet to be investigated. Methods: This was a single-center retrospective observational study involving 134 children who were admitted to the hospital with both abdominal pain and vomiting. The reference standard for appendicitis was defined by computed tomography scanning. The diagnostic performance of “abdominal pain before vomiting” was calculated and compared to those of the Alvarado score and pediatric appendicitis score. Results: The diagnostic performance of “abdominal pain before vomiting” was as follows: sensitivity of 75.3% (95% confidence interval [CI], 64.7–83.6), specificity of 25.0% (95% CI, 15.5–36.7), positive likelihood ratio of 1.00 (95% CI, 0.82–1.22), negative likelihood ratio of 0.99 (95% CI, 0.54–1.79), and diagnostic odds ratio of 1.02 (95% CI, 0.46–2.25). In contrast, the Alvarado score and pediatric appendicitis score (with a threshold of 4 points) demonstrated favorable sensitivity (98.3% [95% CI, 92.4–99.6]), negative predictive value (94.6% [95% CI, 78.4–98.8]), negative likelihood ratio (0.04 [95% CI, 0.01–0.23]), and diagnostic odds ratio (49.9 [95% CI, 6.88–243.2]). Conclusion: In this study, “abdominal pain before vomiting” was associated with poor diagnostic performance for ruling out acute pediatric appendicitis. Thus, the diagnosis of acute appendicitis in the pediatric population should be made based on existing validated scoring systems such as the Alvarado score and pediatric appendicitis score.